Maternal and Fetal Determinants of Caesarean Section Delivery - Cut Yuliza Sutifa; Maidar Maidar; Nurjannah Nurjannah; Hermansyah Hermansyah; Radhiah Zakaria (GLOBAL HEALTH SCIENCE GROUP, 2026)
Maternal, infant, and toddler mortality rates remain a serious public health problem in Indonesia. One effort to reduce these rates is by ensuring safe delivery services, both vaginally and through cesarean sections (CS). Although normal delivery is preferred, the trend of cesarean sections has continued to increase in recent decades. Sultan Iskandar Muda Regional Hospital, as a type C hospital in Nagan Raya Regency, Aceh, records an increase in childbirth cases every year. This study aims to analyze the determinants that influence cesarean section procedures at the hospital. This study uses an explanatory sequential design. This type of quantitative research with a cross-sectional design was conducted using patient medical records. The population is all data on mothers who gave birth by cesarean section at Sultan Iskandar Muda Regional Hospital, taken within a 3-month period, namely October - December 2024, a total of 324 mothers giving birth by cesarean section. The sampling method used the total population with a sample size of 324 respondents. While qualitative research with a phenomenological approach, conducted by interview using interview guidelines, the method of collecting informants using purposive sampling with a total of 7 informants. The results of quantitative research show that the most dominant relationship between cesarean section is prolonged labor (OR: 701.40; 95%CI: 98.02-5019.20; p value: 0.0001), the occurrence of PEB (OR=446.33; 95%CI=21.62-9214.06; p=0.0001) and term birth (OR=35.76; 95%CI=0.29-4446.35; p=0.146) at Sultan Iskandar Muda Regional Hospital, Nagan Raya Regency. The results of qualitative research show that non-medical factors that play a role in cesarean section are fear of pain and complications during normal delivery. Prolonged labor is the most dominant factor with cesarean section. Therefore, health workers at community health centers are expected to provide positive support in the form of positive affirmations to pregnant women, such as deep breathing and relaxation exercises to reduce pain. Strengthen education programs and routine pregnancy check-ups at primary health care facilities to detect risk factors early and prevent childbirth complications.